Kerahasiaan Rekam Medis dalam Pelaksanaan Pelepasan Informasi Rekam Medis di Rumah Sakit : Literature Review - indah muflihatin; alifia tirta ramadhanti; demiawan rachmatta putro mudiono; selvia juwita swari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Document of medical records are owned by health care facilities and the contents of medical records are owned by patients. Release of medical record information must be carried out with the approval from the leader of hospital, based on terms and conditions. Implementation in several hospitals still found problems which could resulting the leakage of medical records. The aims of this study is analyzing the release of medical record based on 3 factors, such as man, facilities, and methods. This is literature review research which uses articles on the online databases of Google Scholar, Crossref, Garuda Portal, and Microsoft Academic. Search and selection resulted in 24 selected articles. The results of the study explain that in the man factor the medical record officer becomes a facilitator in releasing medical record information. Facilities factor, the requirements that must be attached are official permit from suppliant. Method factor, the information release procedure begins with the submission of requirements, processing the request, and submitting the results to the applicant. Problems that often occur in the release of medical record information consist of incomplete requirements, medical record officers did not comprehend the procedure, and Standard Operating Procedures were not yet available. Suggestions for improvements which could be made include providing training to medical record officers, making x-banners of flow and procedures for releasing medical record information, and reinforcing or updating Standard Operating Procedures.